Worsened hypertension control induced by aripiprazole - Yasui-Furukori N (Dove Medical Press, 2013)
Norio Yasui-Furukori, Akira Fujii Department of Neuropsychiatry, Graduate School of Medicine, Hirosaki University, Hirosaki, Japan Abstract: Aripiprazole is widely used in the treatment of schizophrenia and bipolar disorders. Although antipsychotics generally have hypotensive effects, two cases were identified that demonstrated hypertension during the switch from other antipsychotics to aripiprazole. The hypertensive state of these patients recovered after switching back to other antipsychotics, and these cases suggest that aripiprazole may lead to hypertension. Keywords: hypertension, aripiprazole, dopamine antagonist, 5-HT1a